Factors influencing 21st century teaching among secondary school teachers in Selangor, Malaysia - Mohamad, Azlida; Sulaiman, Tajularipin; Mohd Ayub, Ahmad Fauzi (Human Resource Management Academic Research Society, 2023)
Students’ 21st century skills can be enhanced through specific teaching practices such as 21st century teaching. The concept of 21st century teaching is student-centred learning. Yet, several past studies have highlighted the lack of 21st century teaching in practice since teachers prefer to implement a teacher-centred approach. This study aims to determine the effect between four factors, which are pedagogical knowledge, content knowledge, technological knowledge, and critical thinking dispositions towards 21st century teaching among 332 secondary school teachers in Selangor, Malaysia. This study employed the causal relationship design with proportional stratified random sampling. For data collection, a questionnaire was used. Inferential statistical analysis was executed to determine the direct effect through Structural Equation Modelling by using the Analysis of Moment Structure software. The findings showed that pedagogical knowledge, content knowledge, technological knowledge, and critical thinking dispositions had a significant direct effect on 21st century teaching. The findings showed that teachers who have a high level of pedagogical knowledge, technological knowledge, and critical thinking dispositions support them to execute 21st century teaching. However, teachers’ content knowledge showed a negative significant direct effect on 21st century teaching, which means that a high level of content knowledge leads to hesitations in implementing 21st century teaching. As a conclusion, the direct effect model of the current study showed that these four factors contributed to 52 percent in variance for 21st century teaching, indicating that this model can be implemented to secondary school teachers in Selangor to improve the 21st century teaching practice.